Prevalence of oral lesions in pemphigus vulgaris: a retrospective study - K. N., Vinay; Afshan, Gouhare (International Journal of Research in Dermatology, 2019)
Background: Pemphigus vulgaris is an autoimmune vesiculobullous disease characterized by vesicles and or bullae affecting skin and mucosa. Oral lesions are the first manifestation of the disease in majority of cases according to literature. This study is conducted to know the prevalence of oral lesions in pemphigus vulgaris patients at the time of presentation. Methods: This was a retrospective study. Departmental records were evaluated from January 2013 to January 2018. All the demographic data of pemphigus vulgaris patients at the time of first presentation, duration of disease, were assessed and tabulated. The clinical data of these patients during their subsequent visits to clinic were assessed for development of new oral lesions during course of disease. Results: Total number of patients were 55. The mean age was 42.5 years. 12 (21.8%) were males and 4 (78.1%) were females. Out of 55 patients 37 (67.27%) cases had oral involvement and 18 (32.72%) cases did not have oral lesions at the time of presentation. Out of 37 patients who had oral lesions, 34 (91.89%) patients had both oral and skin lesions and 3 (08.10%) patients had only oral lesions at the time of presentation. Out of the18 patients with no oral lesions, 3 (16.66%) patients developed oral lesions within 3 months. Total number of patients with oral lesions out of 55 were 40 (72.7%). Conclusions: Our study shows that oral lesions as initial manifestation of pemphigus vulgaris is 67.2%.